2018
DOI: 10.1371/journal.pone.0205235
|View full text |Cite
|
Sign up to set email alerts
|

A case study of well child care visits at general practices in a region of disadvantage in Sydney

Abstract: IntroductionWell-Child Care (WCC) is the provision of preventive health care services for children and their families. Prior research has highlighted that several barriers exist for the provision of WCC services.ObjectivesTo study “real life” visits of parents and children with health professionals in order to enhance the theoretical understanding of factors affecting WCC.MethodsParticipant observations of a cross-sectional sample of 71 visits at three general practices were analysed using a mixed-methods appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The US study found that more behavioural and developmental concerns were detected using PEDS and generated more referrals. (13) Outcomes from our study were limited by small numbers of "positive" PEDS screening questionnaires, but our qualitative research, and that of others, (14) suggest that knowledge of outcomes of screening is important for clinicians to remain motivated.…”
Section: Discussionmentioning
confidence: 89%
“…The US study found that more behavioural and developmental concerns were detected using PEDS and generated more referrals. (13) Outcomes from our study were limited by small numbers of "positive" PEDS screening questionnaires, but our qualitative research, and that of others, (14) suggest that knowledge of outcomes of screening is important for clinicians to remain motivated.…”
Section: Discussionmentioning
confidence: 89%
“…Comments from some clinicians in this study reflected reasons uncovered by other researchers that may explain a reluctance to participate in screening: an over-reliance on clinical impressions [ 21 , 22 ] failure to recognise parents’ concerns [ 21 , 23 ] and a lack of knowledge about the benefits of validated screening tools. [ 7 , 24 ]. Garg et al highlight the need for further training and recommend practice nurse support for GPs conducting developmental screening [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 24 ]. Garg et al highlight the need for further training and recommend practice nurse support for GPs conducting developmental screening [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mixed-methods approach is thought to provide a more complete basis for complex clinical and policy decision-making than that currently offered by single method reviews ( 4 ). It was particularly appropriate for the present review question, as swaddling is not only a physiological intervention but also a social one; its application differs across and within cultures according to numerous diverse factors such as tradition, health professional advice, policy recommendations, fashion and personality ( 5 – 8 ). The objective of this mixed-methods approach is therefore to integrate a quantitative estimation of swaddling's “effectiveness” via measures of infant sleep duration and arousal, with a more qualitative understanding from the perspective of the implementers of the intervention (usually parents), increasing the relevance of the review for policy and practice.…”
Section: Review Protocolmentioning
confidence: 99%